The solidarity economy - Laville, Jean-Louis (Diverse economies and livable worlds., 2023)
"The Solidarity Economy establishes how the formation of economic solidarities reveals that the boundaries between politics and economics are porous and structured such that politics, ideally a pure expression of ethics and values, is instead integrated with economic concerns. Identifying the power of contemporary social and solidarity movements, Laville examines the history of postcapitalist practices in which democratic demands invade the heart of the economy"--